2001
DOI: 10.1046/j.1365-2133.2001.04379.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of diagnostic criteria for atopic dermatitis: validity of the criteria of Williams et al. in a hospital-based setting

Abstract: The diagnostic efficiency of the criteria of Williams et al. was basically similar to those of Hanifin and Rajka and of Kang and Tian in our out-patient settings. However, those of Williams et al. were easier to apply and required no invasive tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 16 publications
0
34
0
1
Order By: Relevance
“…It is worthwhile to note that a previous report from a hospital-based setting has suggested that the UKWP criteria may be adequate for Chinese patients among all ages. 24 However, in their report, the number of adult patients included was small (17 patients with AD aged [ 16 years) and may not adequately reflect the validity of the UKWP criteria for adults.…”
Section: Discussionmentioning
confidence: 95%
“…It is worthwhile to note that a previous report from a hospital-based setting has suggested that the UKWP criteria may be adequate for Chinese patients among all ages. 24 However, in their report, the number of adult patients included was small (17 patients with AD aged [ 16 years) and may not adequately reflect the validity of the UKWP criteria for adults.…”
Section: Discussionmentioning
confidence: 95%
“…7 The criteria of Hanifin and Rajka 7 have been considered as a gold standard for AD diagnosis for the last 20 years. 18 Its simplified version, the UK Working Party's criteria, is more suitable for epidemiologic studies, and has been validated in large investigations with both high sensitivity and specifity. 8,18,19 Apparently, there is no problem in detecting early-onset AD according to these criteria.…”
Section: Discussionmentioning
confidence: 99%
“…18 Its simplified version, the UK Working Party's criteria, is more suitable for epidemiologic studies, and has been validated in large investigations with both high sensitivity and specifity. 8,18,19 Apparently, there is no problem in detecting early-onset AD according to these criteria. However, this study showed that approximately one fourth of patients could not be given the diagnosis of adult-onset AD according to UK Working Party's criteria in its current form.…”
Section: Discussionmentioning
confidence: 99%
“…[4] These criteria have been used worldwide for the last 30 years in diagnosing AD. [5] Hanifin and Rajka require the assessment of 27 separate criteria (4 major and 23 minor). This results in a complex daily practice.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the sensitivity and specificity of the UK Working Party's criteria are in good agreement with those of Hanifin and Rajka. [5]…”
Section: Introductionmentioning
confidence: 99%